2013
DOI: 10.1007/s00126-013-0494-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship between silver–lead–zinc mineralization in the Wutong deposit, Guangxi Province and Mesozoic granitic magmatism in the Nanling belt, southeast China

Abstract: More than 50 % of the world's total reserves of tungsten are in China and most tungsten deposits are located in the Nanling range in southeast China. This study explores the potential genetic relationship between tungsten-tin (W-Sn) mineralization and shallower Ag-Pb-Zn deposits in the Nanling range based on data from the Wutong deposit, Guangxi Province. The lead, oxygen, carbon, sulfur, and strontium isotopic compositions of minerals at Wutong indicate that a single crustal-derived fluid was responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Bodnar et al (1985a) quantitatively described the effect of trapping multiple fluid phases in the epithermal environment and showed that trapping of only a few volume percent vapor along with the liquid would result in Th that was several tens of degrees higher than the trapping temperature. Similarly, Lecumberri-Sanchez et al (2014) show that many fluid inclusions in the porphyry copper environment that homogenize by halite dissolution are the result of trapping halite along with liquid. Accordingly, we note that in our study of the Bingham Canyon deposit, FIAs composed of inclusions that homogenize by halite dissolution generally show the greatest variability in T h in the deposit.…”
Section: Potential Causes For Th Variation Within Fiasmentioning
confidence: 94%
“…Bodnar et al (1985a) quantitatively described the effect of trapping multiple fluid phases in the epithermal environment and showed that trapping of only a few volume percent vapor along with the liquid would result in Th that was several tens of degrees higher than the trapping temperature. Similarly, Lecumberri-Sanchez et al (2014) show that many fluid inclusions in the porphyry copper environment that homogenize by halite dissolution are the result of trapping halite along with liquid. Accordingly, we note that in our study of the Bingham Canyon deposit, FIAs composed of inclusions that homogenize by halite dissolution generally show the greatest variability in T h in the deposit.…”
Section: Potential Causes For Th Variation Within Fiasmentioning
confidence: 94%
“…Mine tailings repositories are unwanted and uneconomic materials from the mineral processing deposited exposure in the air. Tailings often contain elevated concentrations of metal(loid)s, which are potentially toxic (Lecumberri-Sanchez et al, 2014;Hudson-Edwards, 2016). Abandoned nonferrous metal(loid) tailings (i.e., facilities having no operator or successor) have received considerable attention around the world because they represent a risk for the environment and human health (Aleksandrovskii et al, 2015;COM, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Three proposed wolframite standards of MTM, YGX, and WT are more homogeneous than others, but also have variable U and common Pb shown in the Tera-Wasserburg Concordia diagram in previous and our studies. 10,20,21,23 Moreover, they were with different ID-TIMS U-Pb ages of 334.4 AE 1.7 and 316.7 AE 5.8 Ma, 152.8 AE 2.0 and 160.9 AE 0.7 Ma, and 95.2 AE 1.0 and 104.3 AE 0.5 Ma. [17][18][19][20]23 Thus, if there are no concordant YGX spots, a combined calibration method using wolframite YGX and NIST glasses (e.g., NIST612) to correct the mass fractionation of 238 U/ 206 Pb and 207 Pb/ 206 Pb isotope ratios of the unknowns, respectively, is to be used.…”
Section: Calibration Strategy and Data Reductionmentioning
confidence: 99%
“…17)), and hübnerite WT (95.2 AE 1.0 Ma (ref. 20)), can used to calibrate these wolframite-type minerals. However, whether these reference materials can be used to calibrate scheelite or whether matrix effects exist between scheelite and wolframite is still unclear.…”
Section: Introductionmentioning
confidence: 99%